2008
DOI: 10.1111/j.1600-0854.2008.00785.x
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitylation is Required for Degradation of Transmembrane Surface Proteins in Trypanosomes

Abstract: †These authors contributed equally to this work.The surface of Trypanosoma brucei is dominated by glycosyl-phosphatidylinositol (GPI)-anchored proteins, and endocytosis is clathrin dependent. The vast majority of internalized GPI-anchored protein is efficiently recycled, while the processes by which transmembrane domain (TMD) proteins are internalized and sorted are unknown. We demonstrate that internalization of invariant surface glycoprotein (ISG)65, a trypanosome TMD protein, involves ubiquitylation and als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
91
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 59 publications
(98 citation statements)
references
References 58 publications
7
91
0
Order By: Relevance
“…An in trans decrease in expression levels of ESCRT I (Vps23 and Vps28) and retromer complex (Vps26) proteins on Rab28 knockdown suggests a functional connection between Rab28, ESCRT and retromer. The effects on ESCRT are fully consistent with the observed partial protection of ISG65 and ISG75, as both require ubiquitylation for turnover and, hence, are probably sorted by the ESCRT system (Chung et al, 2008;Leung et al, 2011). The effects on the Rab11 recycling compartment suggest increased cycling of cargo between endosomes, as reported upon silencing of Vps26 and Vps23 in mammalian cells (Seaman, 2004;Razi and Futter, 2006;Raiborg et al, 2008).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…An in trans decrease in expression levels of ESCRT I (Vps23 and Vps28) and retromer complex (Vps26) proteins on Rab28 knockdown suggests a functional connection between Rab28, ESCRT and retromer. The effects on ESCRT are fully consistent with the observed partial protection of ISG65 and ISG75, as both require ubiquitylation for turnover and, hence, are probably sorted by the ESCRT system (Chung et al, 2008;Leung et al, 2011). The effects on the Rab11 recycling compartment suggest increased cycling of cargo between endosomes, as reported upon silencing of Vps26 and Vps23 in mammalian cells (Seaman, 2004;Razi and Futter, 2006;Raiborg et al, 2008).…”
Section: Discussionsupporting
confidence: 73%
“…We were unable to detect any significant change in ISG65 or ISG75 levels on the surface of the cells by FACS analysis, but as we did not have an accurate estimate of relative internal and external pool sizes, this might reflect changes in a comparatively small intracellular pool (data not shown). Previous analysis demonstrated that, in common with higher eukaryotes, turnover of ubiquitylated proteins is dependent on the ESCRT pathway (Chung et al, 2008), so we propose that the increase in intracellular ISG65 and ISG75 following Rab28 depletion is due to failure to progress to the lysosome, similar to the effects of Rab28 RNAi on both ConA and TLF.…”
Section: Rab28 Function In Endocytosis 3775mentioning
confidence: 60%
“…However, we previously found that ISG65 is present on both cell surface and endosomal membranes and turned over significantly more rapidly than VSG, suggesting differential sorting (7). More recently, we demonstrated that lysine residues in the ISG65 cytoplasmic domain are important for regulating trafficking and stability in vivo (8). Furthermore, we showed that this was mediated by a ubiquitin-and ESCRTdependent mechanism (8,25).…”
mentioning
confidence: 82%
“…Furthermore, we found that RNAi knockdown of T. brucei Vps5 resulted in a modest but significant decrease to intracellular levels of ISG75 (Fig. 11C), a transmembrane protein that traffics through the endosomal system and undergoes ubiquitin-dependent degradation (Chung et al, 2008;Leung et al, 2008). The decrease in ISG75 endosome-associated staining is at least in part due to accelerated turnover, and cannot simply be attributed to defective uptake, as T. brucei Vps5 RNAi 1502 Journal of Cell Science 124 (9) leads to more rapid degradation (Fig.…”
Section: Localisation and Functional Analysis Of The Retromer Complexmentioning
confidence: 98%